Enhancing local content in Uganda's oil and gas industry - Ritwika Sen (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
This paper analyses policy options to promote local content in Uganda as it transitions into an oil-producing country. It contends that productive linkages between oil and gas exporters and domestic suppliers in a range of "connected" goods and services sectors can be a source of broad-based economic growth. However, the success of policy initiatives or extensive regulatory requirements will ultimately hinge on domestic supplier capabilities to overcome barriers to entry into the global industry. The analysis comprises an evaluation of existing local content policies in Uganda, a mapping of the natural resource value chain, and an assessment of domestic firm capabilities to supply the anticipated demand for goods and services from the oil and gas industry.
Keywords: O13; O14; O25; O55; 330; firm capabilities; local content; oil and gas; tax administration data; Uganda